1963
DOI: 10.1037/h0045407
|View full text |Cite
|
Sign up to set email alerts
|

Student-teacher characteristics from the pupils' viewpoint.

Abstract: Invariance of factor structure was demonstrated across 3 semester subsamples and across teacher-sex, and factorscore reliabilities were computed. Female teachers were higher than males on Dimensions I and V. Correlations with 2 attitude inventories were low, but significant. Relationships of factor-scores to supervisorrated effectiveness were linear and positive for Factors I, II, and IV, except for a curvilinear effect with males on Factor I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
1

Year Published

1968
1968
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 3 publications
1
12
0
1
Order By: Relevance
“…Though no one would argue seriously that the pupils are inevitably the best judges of teacher's behavior and performance. there are a priori reasons about the reliability of pupils' observations and ratings as well as research data which support this notion (13,17).…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Though no one would argue seriously that the pupils are inevitably the best judges of teacher's behavior and performance. there are a priori reasons about the reliability of pupils' observations and ratings as well as research data which support this notion (13,17).…”
mentioning
confidence: 69%
“…In a similar study with student teachers Veldman and Peck (17) found that the relationship between the student teachers' attitudes as measured by the California Psychological Inventory and evaluations by the pupils was minor. Probably these self-report personality inventories standardized on the general population do not provide a sufficient degree of differentiation for within-a-group individuals.…”
Section: Discussionmentioning
confidence: 94%
“…Further analysis of the thirty questionnaire items revealed a strong mathematical relationship between certain questions, rather along the lines of the effects noted by Veldman & Peck (1963), Beck (1967) and Coats & Swierenga (1972). Logically enough, the responses to the three questions relating to the description of the lesson (ranging from 'boring' to 'exciting') and the degree to which the children had enjoyed 'what they learned' or 'what they had to do' showed a close relationship.…”
Section: Perception Of Student Teachersmentioning
confidence: 87%
“…Les quelques écrits relatifs à la perception des élèves à l'égard des comportements d'enseignement de leur s ta-giaire ont mis l'accent exclusivement sur l'évaluation de la performance de ces derniers (Cortis et Crayson, 1978;Denton, 1977;Meighan, 1974Meighan, , 1978Veldman, 1970;Veldman et Peck, 1963). La plupart de ces études portent sur l'éva-luation de la performance des stagiaires à partir des listes de comportements et de traits de personnalités qui sont fournis par les chercheurs.…”
unclassified